2015
DOI: 10.14488/bjopm.2015.v12.n1.a6
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of Plant Maintenance Management Practices: Role of Six Sigma Approach

Abstract: Today, only those companies which are capable of permanent and fast adaptation to quickly-changing conditions can survive. Six Sigma is at the top of the agenda for many manufacturing companies that try to reduce cost, process variability and improve productivity. In order for a company to remain competitive and maintain maximal efficiency and availability of all its plants and machinery, what is needed is an approach different from the traditional concept of doing plant maintenance. In this paper an attempt i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The DMAIC deployment offers a company a higher success probability when it achieves the full commitment of the organization's top management. Using DMAIC, it is possible to identify and solve problems that occurred in operations, processes, products, or services, to satisfy internal and external consumers of the company (Pophaley;Vyas, 2015;Pinto et al, 2017).…”
Section: Dmaic Methodologymentioning
confidence: 99%
“…The DMAIC deployment offers a company a higher success probability when it achieves the full commitment of the organization's top management. Using DMAIC, it is possible to identify and solve problems that occurred in operations, processes, products, or services, to satisfy internal and external consumers of the company (Pophaley;Vyas, 2015;Pinto et al, 2017).…”
Section: Dmaic Methodologymentioning
confidence: 99%
“…From the social perspective of sustainability, many authors indicate the positive impact of maintenance on the creation of a safe and healthy working environment [33]. As far as environmental issues are concerned, maintenance activities are aimed, among others, at reducing the energy consumption of machines and devices, minimizing the production of toxic waste, and effective use of spare parts and consumables [32,46,73].…”
Section: Maintenance Importance In Manufacturingmentioning
confidence: 99%
“…By achieving an optimal product mix, an enterprise is able to increase profits and minimize production costs. Musaki revealed that by achieving optimal product mix, enterprises were able to increase net profit 2 Literature Review Theory of Constraints (TOC) concept has been widely discussed to solve various problems in the various fields such as to increase net profit, to improve productivity, to reduce the production costs, to achieve service excellence, to improve the efficiency of business processes, to regulate the distribution of the logistics sector, to optimize the maintenance of law permits ownership of motor vehicles, weapons, and pets [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%